Sliding mode control for an active magnetic bearing system subject to base motion - Kang, Min Sig; Lyou, Joon; Lee, Jong Kwang (Mechatronics (Oxford), 2010)
This paper describes the application of an active magnetic bearing (AMB) system to levitate the elevation axis of an electro-optical sight mounted on a moving vehicle. In this type of system, it is desirable to retain the elevation axis in an air–gap between magnetic bearing stators while the vehicle is moving. A sliding mode control is applied to increase robustness to model uncertainties and to reduce disturbance responses. To ensure the authority of sliding mode control, model parameter uncertainties of AMB systems are analysed and reachability to sliding surface has been verified. The sliding surfaces are designed such that the poles of the closed-loop system locate at desired locations. The proposed control is applied to a 2-DOF active magnetic bearing system subject to base motion. The feasibility of the proposed technique is verified with experimental results.